High-Throughput Screen for Identifying Small Molecules That Target Fungal Zinc Homeostasis - Simm, Claudia; Luan, Chi-Hao; Weiss, Eric; O'Halloran, Thomas (PLOS ONE, 2011)
Resistance to traditional antifungal drugs has increased significantly over the past three decades, making identification of novel antifungal agents and new targets an emerging priority. Based on the extraordinary zinc requirement of several fungal pathogens and their well-established sensitivity to zinc deprivation, we developed an efficient cell-based screen to identify new antifungal drugs that target the zinc homeostasis machinery. The screen is based on the zinc-regulated transcription factor Zap1 of Saccharomyces cerevisiae, which regulates transcription of genes like the high-affinity zinc transporter ZRT1. We generated a genetically modified strain of S. cerevisae that reports intracellular zinc deficiency by placing the coding sequence of green fluorescent protein (GFP) under the control of the Zap1-regulated ZRT1 promoter. After showing that the GFP fluorescence signal correlates with low intracellular zinc concentrations in this strain, a protocol was developed for screening small-molecule libraries for compounds that induce Zap1-dependent GFP expression. Comparison of control compounds and known modulators of metal metabolism from the library reveals a robust screen (Z′ = 0.74) and validates this approach to the discovery of new classes of antifungal compounds that interfere with the intracellular zinc homeostasis. Given that growth of many pathogenic organisms is significantly impaired by zinc limitation; these results identify new types of antifungal drugs that target critical nutrient acquisition pathways.